Voronoi cell finite element model to simulate crack propagation in porous materials. (October 2021) - Zhang, Rui; Guo, Ran
Abstract: Voronoi cell finite element models (VCFEM) containing pores and various cracks were developed in this study to simulate crack propagation in porous materials. In addition to polynomial terms, singular items were inserted into the stress function to capture the stress concentration at the tip of the crack. During crack propagation, the Voronoi element type changes such that an element may contain an internal crack, an edge crack, a bridge crack, or other types of cracks in addition to a pore. Functional of the element containing both bridge crack and external crack were derived, and a crack propagation program was developed to execute a mesh division algorithm for crack propagation from one element to another. The results of the tests showed that the proposed method could effectively be used to mitigate crack propagation.